Answer: $103.88
Step-by-step explanation:
98*0.06=5.88 <--- total tax charged
98+5.88=103.88 <--- add tax to price
Answer:
![x=12\\y=\frac{13}{3}](https://tex.z-dn.net/?f=x%3D12%5C%5Cy%3D%5Cfrac%7B13%7D%7B3%7D)
Step-by-step explanation:
For it to be a parallelogram, opposite sides have to be of same length.
Using the expressions given, we can make 2 equations:
<u>Equation 1:</u>
![OL=NM\\3y-6=x-5\\-x+3y=1](https://tex.z-dn.net/?f=OL%3DNM%5C%5C3y-6%3Dx-5%5C%5C-x%2B3y%3D1)
<u>Equation 2:</u>
![ON=LM\\8x-8=7x+4\\](https://tex.z-dn.net/?f=ON%3DLM%5C%5C8x-8%3D7x%2B4%5C%5C)
<em>Solving equation 2, we have x:</em>
![8x-8=7x+4\\8x-7x=4+8\\x=12](https://tex.z-dn.net/?f=8x-8%3D7x%2B4%5C%5C8x-7x%3D4%2B8%5C%5Cx%3D12)
<em>Plugging this value of x into equation 1, we can solve for y:</em>
![-x+3y=1\\-(12)+3y=1\\-12+3y=1\\3y=13\\y=\frac{13}{3}](https://tex.z-dn.net/?f=-x%2B3y%3D1%5C%5C-%2812%29%2B3y%3D1%5C%5C-12%2B3y%3D1%5C%5C3y%3D13%5C%5Cy%3D%5Cfrac%7B13%7D%7B3%7D)
So,
![x=12\\y=\frac{13}{3}](https://tex.z-dn.net/?f=x%3D12%5C%5Cy%3D%5Cfrac%7B13%7D%7B3%7D)
Google it.... <em> </em>I just did and there is a video.
Answer:
alr so basically what you want to do is multiply the numbers to get the answer
Step-by-step explanation:
Answer:
a= 5 and b=1
Step-by-step explanation:
To solve, we will follow the steps below:
2x + 3y = 7
(a-b)x + (a+b)y = 3a + b - 2
We should note that since it has infinitely many solutions then,
![\frac{a_{1} }{a_{2} } = \frac{b_{1} }{b_{2} } = \frac{c_{1} }{c_{2} }](https://tex.z-dn.net/?f=%5Cfrac%7Ba_%7B1%7D%20%7D%7Ba_%7B2%7D%20%7D%20%20%20%3D%20%20%5Cfrac%7Bb_%7B1%7D%20%7D%7Bb_%7B2%7D%20%7D%20%20%3D%20%5Cfrac%7Bc_%7B1%7D%20%7D%7Bc_%7B2%7D%20%7D)
Hence
2/a-b = 3/a+b = 7/3a +b-2
2/a-b = 3/a+b
cross-multiply
3(a-b) = 2( a+b)
open the bracket
3a - 3b = 2a + 2b
collect like term
3a - 2a = 2b + 3b
a = 5b -------------------------------------------(1)
Similarly
3/a+b = 7/3a +b-2
cross-multiply
7(a+b) = 3(3a+b -2)
7a + 7b = 9a + 3b -6
take all the variables to the left-hand side of the equation
7a - 9a+ 7b-3b = -6
-2a + 4b = -6 ---------------------------------(2)
but a = 5b
substitute a= 5b in equation (2) and solve for b
-2(5) + 4b = -6
-10 + 4b = -6
add 10 to both-side of the equation
-10 + 10+ 4b = -6+10
4b = 4
divide both-side of the equation by 4
b = 1
substitute b= 1 in equation (1)
a = 5b
a =5(1)
a=5
Therefore, a= 5 and b=1